CONTRASTIVE ANALYSIS BETWEEN INDONESIAN AND ENGLISH IN ADJECTIVE FOR OPINIONS - Situngkir, Artha Yuni Trimedia; Situmeang, Khaterina Vonbora; Hutauruk, Rut Maria (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2022)
This study concerns the differences between the two languages, with Indonesian as the source language and English as the target language. And the problem limitation is focused on analyzing the differences in adjectives for feelings between English and Indonesian in Beauty and the Beast's video, https://youtu.be/IMrMILXMUaQ especially those that concentrate on the lexis (the total number of words in the language). This research used descriptive qualitative research. The technique of analyzing data used in this study is based on contrastive analysis from lexis in an adjective for feeling. Researchers searched and found data from YouTube. After that, the researcher analyzes each word from the story of Beauty and the Beast, which is included in the adjective for opinion. And then, the researcher looks for words that have the same meaning or are included in the adjective for opinion by using an English dictionary, then compares with the same word in Indonesian using the Indonesian dictionary. The results of the analysis show that there are 4 types of adjectives found in the video based on the rules, namely: adjective for opinion, adjective for general size, adjective for age, and adjective for material. To compare the number of words in Indonesian and English, the researcher focused on comparing the types of adjectives for opinion in the video. There are 21 words found in the text to compare, and each one has a different number of lexis.